Morphological and physicochemical evaluation of the propranolol HCl–Eudragit® RS100 electrosprayed nanoformulations. (19th May 2018) - Garjani, Alireza; Barzegar-Jalali, Mohammad; Osouli-Bostanabad, Karim; Ranjbar, Hamed; Adibkia, Khosro
Abstract: The aim of this study was to fabricate propranolol hydrochloride (Prop. HCl) (as a water-soluble drug):Eudragit ® RS100 (Eud) nanobeads and nanofibres applying the electrospraying method as an economical and one-step technique. Different ratios of Prop. HCl:Eud (i.e. 1:5 and 1:10) at total solution concentrations of 10–20% W/V were investigated. The FE-SEM studies revealed that morphology and size of the samples were highly affected by the solution concentration; so that, the nanobeads (a mean diameter of 82.9 nm) were formed in low concentration and at the highest concentration of the solution, nanofibres (a mean diameter of 232.3 nm) were resulted. Besides the morphological changes, the size of processed nanoformulations was increased with an increment of the solution concentrations. X-ray diffraction results as well as DSC thermograms clearly indicated that the drug crystallinity decreased in the electrosprayed samples. Furthermore, in vitro dissolution test showed that the electrosprayed samples had relatively slower release patterns toward the pure drug and physical mixtures, where the samples with the drug:polymer ratio of 1:10 indicated a faster release rate toward 1:5 ratio; nevertheless, the concentration of the injected formulations did not remarkably impressed the release behaviours. The current study established the suitability of electrospraying method in the fabrication of the water-soluble drugs nanobeads/nanofibres; however, in vivo effectiveness of the prepared nanoformulations should be meticulously considered.